Non-hip and non-vertebral fractures: the neglected fracture sites. Issue 3 (March 2016) - Holloway, K.; Henry, M.; Brennan-Olsen, S.; Bucki-Smith, G.; Nicholson, G.; Korn, S.; Sanders, K.; Pasco, J.; Kotowicz, M.
Abstract Summary Non-hip, non-vertebral fractures (NHNVF) were compared with hip, vertebral and controls. NHNVF were younger and heavier than controls and hip/vertebral fractures in both men and women, respectively. Falls and prior fractures were less common in NHNVF than hip fractures. Glucocorticoid use was lower in NHNVF compared to vertebral fracture (VF) in men. Introduction Although hip fracture (HF) and vertebral fractures (VF) receive the most attention in the literature and are the targeted sites for fracture prevention, non-hip, non-vertebral fracture (NHNVF) sites account for a greater proportion of fractures than the hip or vertebrae. This study aimed to assess risk factors for NHNVF and compare them with those for HF, VF and controls. Methods Incident fractures during 2005–2007 for men and 1994–1996 for women were identified using computerised keyword searches of radiological reports, and controls were selected at random from electoral rolls for participation in the Geelong Osteoporosis Study. Participants aged 60+ years were included in this study. Results Compared to controls, men and women with NHNVF were younger (ORs, 0.90, 95 % CI 0.86–0.94; and 0.96, 0.93–0.98, respectively) and had a lower femoral neck bone mineral density (BMD) T-score (age-adjusted; difference [men] 0.383, P  = 0.002; [women] 0.287, P  = 0.001). Compared to HF, men and women with NHNVF were heavier (difference [men] 9.0 kg, P  = 0.01; [women] 7.6 kg, P  < 0.001). Heavier weight was also a risk factor for women with NHNVF compared to VF (1.03, 1.01–1.06). In men with NHNVF, falls (0.37, 0.14–0.97) and prior fractures (0.38, 0.15–0.98) were less common compared to HF; and glucocorticoid use was less common for NHNVF (0.30, 0.11–0.85) compared to VF. Conclusions Given the high numbers of NHNVF sustained by men and women in this study, fracture prevention strategies should focus on individuals with high risk of sustaining these types of fractures, as well as on individuals who are more likely to sustain a HF or VF.